2021
DOI: 10.1515/biol-2021-0050
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency and cardiovascular risk in type 2 diabetes population

Abstract: This study aims to assess vitamin D deficiency-induced dyslipidemia and cardiovascular disease (CVD) risk in poor glycemic control among type 2 diabetes mellitus (T2DM) patients. This study was carried out among 455 T2DM patients involving poor glycemic control (n = 247) and good glycemic control (n = 208). Fasting plasma glucose (FPG) and HbA1c were measured to assess glycemic control. Cardiac risk ratio, atherogenic index plasma, and atherogenic coefficient were calculated to assess and compare the CVD risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
(38 reference statements)
0
5
0
1
Order By: Relevance
“…The literature supports the inverse relationship between AIP and vitamin D in our study. In another study, Pokhrel et al observed a significant negative correlation between vitamin D with lipid markers and atherogenic variables in a poor glycemic control diabetic population [ 53 ]. Some studies have shown that vitamin D supplementation improves dyslipidemia and atherogenic indices [ 54 ], and may be effective in preventing atherosclerosis [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The literature supports the inverse relationship between AIP and vitamin D in our study. In another study, Pokhrel et al observed a significant negative correlation between vitamin D with lipid markers and atherogenic variables in a poor glycemic control diabetic population [ 53 ]. Some studies have shown that vitamin D supplementation improves dyslipidemia and atherogenic indices [ 54 ], and may be effective in preventing atherosclerosis [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D deficiency can increase the level of PTH , which can increase the risk of cardiovascular diseases such as myocardial hypertrophy and valve calcification by influencing lipid metabolism and increasing inflammation, insulin resistance, hypertension and other mechanisms [ 54 ]. A higher level of vitamin D can increase intestinal calcium absorption, inhibit the absorption of cholesterol, promote the excretion of cholesterol from feces, and reduce the formation of TG [ 55 ]. TAFA5 , CPB1 , and SLCO1B3 were the hub genes in the grey60 module.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the rise of serum levels of vitamin D is found to be associated with improvement of glucose tolerance and better control of diabetes; each rise of 1 ng/ml of vitamin D levels is associated with the decline of HbA1c percentage by 0.09%, signifying the key value of the rise of vitamin D in declining the risk of CVD complications in T2DM patients [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a multifunctional fat-soluble vitamin, consequences of de ciency of vitamin D might not only a ect musculoskeletal metabolism and functions, but it will modulate many other cellular events, such as immunological response, cell proliferation and di erentiation, insulin homeostasis, and metabolic functions as well [2]. us, it might play a vital role in the pathogenesis of insulin resistance, type 2 diabetes mellitus (T2DM), and cardiometabolic complications of T2DM patients [3]. By the e ect of UV light, 7-dehydrocholesterol (provitamin D 3 ) is converted into (cholecalciferol) vitamin D 3 that is transported to the liver with dietary vitamin D 2 to be hydroxylated by the enzyme P 450 vitamin D-25-hydroxylase into 25-hydroxyvitamin D. Furthermore, hydroxylation occurs in the kidney and to less extent in monocytes, placenta, and macrophages, by the enzyme (CYP27B1) 25 ere is growing evidence linking pathognomonic and molecular mechanisms of deficient vitamin D status with the development of T2DM, and it has been postulated that 1,25 dihydroxycholecalciferol or 1,25(OH) 2 D 3 may increase insulin sensitivity, thus resulting in the cellular responsiveness for transportation of glucose [5].…”
Section: Introductionmentioning
confidence: 99%